The relationship between personality and empathy on prosocial behavior among undergraduate students in Klang Valley, Malaysia - Khairol Anwar, Farah Dayana; Ma’rof, Aini Azeqa; Abdullah, Haslinda (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigates the impact of different personality qualities, namely Openness, Conscientiousness, Extroversion, Agreeableness, Neuroticism, and empathy, on prosocial behavior in a sample of 322 adults. The study employed a quantitative research methodology to examine personality traits and prosocial behavior using self-reported measures. Correlation and multiple regression analyses were then conducted to determine the predictive potential of these traits. The examination of levels of prosocial conduct indicated that a majority of individuals displayed elevated tendencies towards engaging in prosocial actions. Similarly, the distribution of personality traits exhibited elevated scores mostly in the dimensions of Conscientiousness and Openness. Correlation research revealed notable positive associations between prosocial conduct and the majority of personality qualities, with empathy being the most prominent factor. Importantly, there was no significant correlation observed between Neuroticism and prosocial conduct. The results of the multiple regression analysis highlighted the importance of empathy in predicting prosocial conduct, transcending the impact of other personality qualities. The regression model explained a significant amount of the variation in prosocial behavior, demonstrating the powerful ability of empathy in conjunction with specific personality traits to make accurate predictions. The study emphasizes the crucial role of empathy in cultivating prosocial behaviors, indicating that interventions targeting the improvement of empathetic abilities could be successful in encouraging prosocial activities in different situations.